2023
DOI: 10.3389/fendo.2023.1126637
|View full text |Cite
|
Sign up to set email alerts
|

Subacute thyroiditis following COVID-19: A systematic review

Abstract: BackgroundSubacute thyroiditis (SAT) is a self-limiting thyroid inflammatory disease occurring specifically after upper respiratory tract infections. Since COVID-19 is a respiratory disease leading to multi-organ involvements, we aimed to systematically review the literature regarding SAT secondary to COVID-19.MethodsWe searched Scopus, PubMed/MEDLINE, Cochrane, Web of Science, ProQuest, and LitCovid databases using the terms “subacute thyroiditis” and “COVID-19” and their synonyms from inception to November 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…A recent study has reported a large amount of thyroiditis in Bengaluru, India, based on a nuclear medicine centers-based study, although the proportion of thyroiditis among thyrotoxicosis was not reported, which may indicate a higher prevalence of subacute thyroiditis in the city [ 12 ]. The coronavirus disease 2019 (COVID-19) epidemic in 2020-2021 and vaccination for COVID-19 might have also contributed to a slightly higher proportion of subacute thyroiditis in the current study [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported a large amount of thyroiditis in Bengaluru, India, based on a nuclear medicine centers-based study, although the proportion of thyroiditis among thyrotoxicosis was not reported, which may indicate a higher prevalence of subacute thyroiditis in the city [ 12 ]. The coronavirus disease 2019 (COVID-19) epidemic in 2020-2021 and vaccination for COVID-19 might have also contributed to a slightly higher proportion of subacute thyroiditis in the current study [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding thyroid diseases, subacute thyroiditis has been reported to have a twofold increased risk of onset in the first 6 months after onset of COVID-19, and subacute thyroiditis after COVID-19 appears to have the same characteristics as those of conventional subacute thyroiditis 21 , 22 . No cases of subacute thyroiditis were found in this study, probably because subacute thyroiditis is a relatively acute condition and is diagnosed and treated by primary care physicians and internists before referral to the outpatient clinic for long COVID at our university hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Subacute thyroiditis (SAT) is a self-limiting and inflammatory thyroid disease, accounting for approximately 5% of all thyroid diseases. SAT often occurs after an upper respiratory tract infection and is probably caused by a viral infection (1)(2)(3)(4). The potentially causative viruses include Coxsackie virus, Echovirus, adenovirus, influenza virus, mumps and rubella virus, parvovirus B19, orthomyxovirus, HIV, Epstein-Barr virus, hepatitis E, measles virus, and the pandemic-spreading severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) since the outbreak of novel coronavirus (COVID-19) in 2019 (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%